Circulating concentrations of glycocalyx degradation products in preeclampsia - Carlberg, Niclas; Cluver, Catherine; Hesse, Camilla; Thörn, Sven-Egron; Gandley, Robin; Damén, Tor; Bergman, Lina (Frontiers in Physiology, 2022)
Background and Objectives Preeclampsia is a multisystem disorder that affects maternal endothelium. The glycocalyx lines and protects the endothelial surface. In severe systemic diseases, like sepsis, it is shed and glycocalyx degradation products can be detected in increased concentrations in plasma. The aim of this study was to compare circulating concentrations of glycocalyx degradation products in degrees of preeclampsia severity. Study design In this observational study, we included women from the South African PROVE biobank. Women were divided into normotensive controls, women with preeclampsia without end-organ complications, women with a single end-organ complication and women with multiple end-organ complications. Plasma samples taken at inclusion after diagnosis (preeclampsia cases) or at admission for delivery (normotensive controls) were analyzed with ELISA for syndecan-1, hyaluronic acid and thrombomodulin and compared between groups. Results Women with preeclampsia (n=47) had increased plasma concentrations of hyaluronic acid (100.3 ng/ml IQR 54.2-204 vs 27.0 ng/ml IQR (13.5-66.6), p<0,001) and thrombomodulin (4.22 ng/ml IQR 3.55-5.17 vs 3.49 ng/ml IQR 3.01-3.68, p=0.007) but not syndecan-1 compared with normotensive women (n=10). There were no differences in plasma concentration in any of the biomarkers in women with preeclampsia with no end-organ complications (n=10) compared with women with preeclampsia and one end-organ complication (n=24). Women with preeclampsia with two or more end-organ complications (n=13) had increased plasma concentrations of thrombomodulin (5.46 ng/ml, IQR 4.85-7.83 vs 4.66 ng/ml, IQR 3.45-4.88, p=0.042) compared with women with preeclampsia and no end-organ complications. Conclusions Thrombomodulin was associated with disease severity and may be valuable for risk-stratifying women with preeclampsia.